Low bioavailability of dietary iron among Brazilian children: Study in a representative sample from the Northeast, Southeast, and South regions - Carlos Alberto Nogueira-; Daniela Prozorovscaia; Elaine M. Bento Mosquera; Elaine M. Bento Mosquera; Fábio da Veiga Ued; Vanessa Caroline Campos (Frontiers Media S.A., 2023)
BackgroundDespite all efforts, iron deficiency anemia remains a serious public health problem among Brazilian children.ObjectiveTo evaluate dietary iron intake and dietary practices that interfere with the absorption of this nutrient from three regions of Brazil.MethodsBrazil Kids Nutrition and Health Study is a cross-sectional dietary intake study in children aged 4-13.9 years old designed to investigate nutrient intakes and gaps of Brazilian children in a representative sample of households from Northeast, Southeast and South regions. Nutrient intake was assessed based on multiple-pass 24-h dietary recall and U.S. National Cancer Institute method was used to estimate usual micronutrients intakes and compliance with Dietary Reference Intakes.ResultsFive hundred sixteen individuals participated in the study (52.3% male). The top three most consumed food sources of iron were products of plant origin. Food sources of animal origin contributed with <20% of the total iron intake. Vitamin C intake was adequate, but the concomitant consumption of food sources of vitamin C with plant food sources of iron was not common. On the other hand, the concomitant intake of plant food sources of iron with food sources of iron chelators (e.g., coffee and teas) was frequent.ConclusionsAdequate iron intake was observed in all three regions in Brazil. Children's diet showed low iron bioavailability and insufficient consumption of food sources of iron absorption stimulants. Frequent presence of iron chelators and inhibitors of iron absorption might help to explain the high prevalence of iron deficiency in the country.